2021
DOI: 10.1515/hc-2020-0128
|View full text |Cite
|
Sign up to set email alerts
|

Para toluenesulfonic acid-catalyzed one-pot, three-component synthesis of benzo[5,6]chromeno[3,2-c]quinoline compounds in aqueous medium

Abstract: A new series of benzo[5,6]chromeno[3,2-c]quinoline derivatives were successfully synthesized using various arylglyoxal monohydrates, quinoline-2,4-dione, and β-naphthol in H2O:EtOH (2:1) as a green solvent in the presence of catalytic amounts p-toluenesulfonic acid as a mild catalyst under reflux conditions with high yields (83–92%). The reaction conditions were optimized in different solvents at variable thermal conditions, and the optimized reaction condition for this synthesis has been reported. The structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In view of the importance of chromenes, Soltani et al have opted for p -TSA-catalysed three-component coupling of different arylglyoxals with quinoline-2,4(1 H ,3 H )-dione and naphthalen-2-ol to produce a series of benzo[5,6]chromeno[3,2- c ]quinolone derivatives in aqueous ethanol medium (Scheme 32). 47 A high yield of products (up to 92%) was isolated within 1–2 hours under reflux conditions. The catalyst p -TSA was expected to free up arylglyoxal from its monohydrate form and catalyse the Knoevenagel condensation between free glyoxal and quinoline enol form.…”
Section: Synthesis Of Fused-heterocyclic Compoundsmentioning
confidence: 98%
“…In view of the importance of chromenes, Soltani et al have opted for p -TSA-catalysed three-component coupling of different arylglyoxals with quinoline-2,4(1 H ,3 H )-dione and naphthalen-2-ol to produce a series of benzo[5,6]chromeno[3,2- c ]quinolone derivatives in aqueous ethanol medium (Scheme 32). 47 A high yield of products (up to 92%) was isolated within 1–2 hours under reflux conditions. The catalyst p -TSA was expected to free up arylglyoxal from its monohydrate form and catalyse the Knoevenagel condensation between free glyoxal and quinoline enol form.…”
Section: Synthesis Of Fused-heterocyclic Compoundsmentioning
confidence: 98%
“…Naser Sadeghpour Orang et al developed three component process for synthesis of Chromeno derivatives 64(a-j) by mixing arylgyloxals 61(a-j), quinoline 2, 4(1H, 3H)-dione (62) and naphthalen-2-ol (63) in a green solvent EtOH: H 2 O (1 : 2) in the presence of catalyst p-toluene sulphonic acid. [32] (Scheme 12) Shailesh R. Shah et al reported a protocol for synthesis of quinoline-1,3-oxazole hybrids 73(a-l). Synthesis was carried out by preparing first starting material 2-aryl-5-methyl-1,3-oxazole-4-cabaldehydes 68(a-f).…”
Section: Chemistryselectmentioning
confidence: 99%
“…The piperidine ring is also considered an important moiety among medicinal chemists due to its diverse therapeutic effects ((analgesic, antihypertensive, CNS depressant antiviral, and bactericidal activity) [11][12][13][14][15][16] . p-Toluene sulfonic acid (p-TSA) is a well-known catalyst in organic synthesis because of its non-toxic/eco-friendly nature, selectivity, easy handling, commercial availability, less cost, and stability [17][18][19][20][21][22][23][24][25][26][27][28][29][30] . Accordingly, the authors decided to perform the titled study.…”
Section: Introductionmentioning
confidence: 99%